1999
DOI: 10.1103/physreve.59.3526
|View full text |Cite
|
Sign up to set email alerts
|

uv continuum emission and diagnostics of hydrogen-containing nonequilibrium plasmas

Abstract: For the first time the emission of the radiative dissociation continuum of the hydrogen molecule (a 3 Σ + g → b 3 Σ + u electronic transition) is proposed to be used as a source of information for the spectroscopic diagnostics of non-equilibrium plasmas. The detailed analysis of excitation-deactivation kinetics, rate constants of various collisional and radiative transitions and fitting procedures made it possible to develop two new methods of diagnostics of: (1) the ground X 1 Σ + g state vibrational temperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 34 publications
1
65
0
Order By: Relevance
“…The simulation of the continuum emission implies the consideration of a repulsive state and thus wavelength dependent transition probabilities assigned to the ro-vibrational quantum number of the upper state. Simulation of the continuum emission is applied successfully at low temperature plasmas for plasma diagnostic purposes; in particular, it has been shown that the vibrational population determines the shape of the continuum emission, whereas the intensity is sensitive to the electron density and temperature [29,30]. Figure 4 shows the spectrum of a hydrogen plasma at a pressure of 3 Pa measured with the VUV spectrometer.…”
Section: Simulation Of Molecular Spectra Using a Corona Modelmentioning
confidence: 99%
“…The simulation of the continuum emission implies the consideration of a repulsive state and thus wavelength dependent transition probabilities assigned to the ro-vibrational quantum number of the upper state. Simulation of the continuum emission is applied successfully at low temperature plasmas for plasma diagnostic purposes; in particular, it has been shown that the vibrational population determines the shape of the continuum emission, whereas the intensity is sensitive to the electron density and temperature [29,30]. Figure 4 shows the spectrum of a hydrogen plasma at a pressure of 3 Pa measured with the VUV spectrometer.…”
Section: Simulation Of Molecular Spectra Using a Corona Modelmentioning
confidence: 99%
“…Optimal values of the rovibronic levels for the triplet electronic states corresponding to principle quantum numbers n = 2, 3 of the united atom are listed in table III. Radiative transitions between those levels are located in visible part of spectra, which is most convenient for spectroscopic studies of non-equilibrium gases and plasmas [4,5]. The expanded version of the table III including all 1050 optimal level values is presented in [46].…”
Section: Experimental Determination Of Wavenumbers For Questionabmentioning
confidence: 99%
“…The analysis of excitation processes such as the determination of the gas temperature and of the degree of dissociation in plasmas containing molecular feed gases, e.g. hydrogen or diborane, was also examined using emission spectroscopy [13][14][15]. Recently, this type of reactor has been used to investigate the chemistry and kinetics in plasmas with admixtures of hydrocarbons and other reactive gases by infrared absorption spectroscopy [16,17].…”
Section: Introductionmentioning
confidence: 99%